Peranan Guru dalam Mengatasi Problematika Penanaman Nilai Kesopanan untuk Meningkatkan Karakter Siswa di SMP Negeri 7 Palopo - Muslikha, Al (Journal of Comprehensive Science, 2025)
Character education plays a significant role in shaping students' noble personalities. One of the essential values to instill is politeness, which includes respect, courtesy, and ethics in social interactions. This study aims to examine the role of teachers in addressing the challenges of instilling the value of politeness at SMP Negeri 7 Palopo. Using a descriptive qualitative approach, this research was conducted through observations and interviews with the school principal, teachers, students, and staff. The findings show that teachers play an active role in instilling politeness through exemplary behavior in speech, actions, and dress. However, challenges such as lack of discipline, disrespect towards teachers, and dishonest behavior among students persist. Proposed solutions include reinforcing politeness through guidance, applying educational punishments, promoting good behavior habits, and enhancing supervision.